Study of collaborative management of supply chain in an IT environment - Yanping Ding (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: This paper identifies collaborative management of supply chain in an IT environment as the object of study. It offers discussion on the current situation and future development of supply chain management, the basic theories of supply chain management, and the comparison between the features of centralized management and collaborative management in an IT environment. It also points out the features and advantages of collaborative management of supply chain in an IT environment. Methodology: By way of analyzing the future development of supply chain management, this paper analyzes the advantages of collaborative management over centralized management. It also explores its implications and its requirements of interaction between onstage and backstage platforms. Findings: This paper lists the seven prominent features of collaborative management of supply chain in an IT environment, including being Internet-based, virtual, interrelated, and so on. In addition, it points out its advantages, such as collaborative decision-making, system-orientation, the establishment of a new cooperative relationship, etc. Application and limitations: This paper is an attempt to call on enterprises to update their current supply management system to collaborative management of supply chain in an IT environment. In this way, they can be more competitive in terms of supply chain. But this paper focuses only on its advantages and does not offer suggestions as to how to establish such a system.
Keywords: 650; supply chain; supply management system; collaborative management; IT